2015
DOI: 10.1039/c5ra10565j
|View full text |Cite
|
Sign up to set email alerts
|

An efficient condensation of substituted salicylaldehyde and malononitrile catalyzed by lipase under microwave irradiation

Abstract: The present work illustrates the condensation of substituted salicylaldehyde and malononitrile catalyzed by lipase under microwave irradiation. The reaction obtains two different products by a delicate control of the substrate molar ratio and reaction time. This protocol has the advantages of high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Further, undesired side-reactions such as oligomerization may occur with relatively low reaction temperatures, and catalyst recovery is challenging. 6 As reported, the Knoevenagel condensation reaction 2,7,8 can take place on ethyl malonate (as substrate) bound to the Wang resin, however, product cleavage requires trifluoroacetic acid, leading to excess pollution when it afforded pure coumarin-3-carboxylic acid derivatives. 9 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, undesired side-reactions such as oligomerization may occur with relatively low reaction temperatures, and catalyst recovery is challenging. 6 As reported, the Knoevenagel condensation reaction 2,7,8 can take place on ethyl malonate (as substrate) bound to the Wang resin, however, product cleavage requires trifluoroacetic acid, leading to excess pollution when it afforded pure coumarin-3-carboxylic acid derivatives. 9 …”
Section: Introductionmentioning
confidence: 95%
“…Further, undesired side-reactions such as oligomerization may occur with relatively low reaction temperatures, and catalyst recovery is challenging. 6 As reported, the Knoevenagel condensation reaction 2,7,8 can take place on ethyl malonate (as substrate) bound to the Wang resin, however, product cleavage requires triuoroacetic acid, leading to excess pollution when it afforded pure coumarin-3-carboxylic acid derivatives. 9 To overcome those drawbacks mentioned above, numerous efforts have been made to develop better heterogeneous Knoevenagel catalysts, for example, metal-salt, nanoparticle catalyst, modied zeolites, ionic liquids or magnetic base analogues.…”
Section: Introductionmentioning
confidence: 95%
“…The reaction of salicylaldehydes with malononitrile revealed that a delicate control of solvent, temperature and ratio of reagents can determine the incorporation of one [12][13][14] , two, 15,16 or three 17 units of malononitrile in the final product (Figure 1, 1b, 2, 3b or 4) and also generate a dimeric product 15 (5) after stirring for one day in basic medium at room temperature.…”
Section: Figurementioning
confidence: 99%
“…It is well recognized that Knoevenagel condensations are generally carried out with aromatic aldehydes as substrates . Moreover, Wang et al reported a protocol based on lipase‐catalyzed condensation of substituted salicylaldehyde under microwave irradiation . To the best of our knowledge, only limited examples with aliphatic aldehydes have been reported, and all of them are limited to α,β‐unsaturated derivatives , .…”
Section: Introductionmentioning
confidence: 99%